Analysis of agriculture and dairy-related driving forces for future farming in Haryana - jose, elizabeth; K.Ponnusamy (Indian Journal of Dairy Science, 2025)
Declining size of landholdings without any alternative income augmenting opportunity can lead to dramatic drop in farm income and cause agrarian distress. The reduction of poverty and sustainability of economic growth in India are directly correlated with crop and associated farm operations. Growing concern for food and nutritional security is giving an impetus to integrate the cropping fields with alternate income generating activities. Haryana is known as ‘bread basket’ of India. The state has diverse agro-ecology and cropping pattern. Delphi technique was used to find out the future scenario of farming sector in Haryana state. A total of 60 respondents was selected for Delphi survey. The driving forces were judged independently by each expert on Likert type scale. An index is developed to identify key driving forces, was obtained by taking average of index value of importance of the driving forces and probability of driving forces. Study indicates that, in the near future, there will be increased efforts to reduce the use of pesticides and insecticides in agriculture. In the dairy sector, there will be greater scope for mechanization in the upcoming days. Study concludes that changes in consumption pattern, increasing market orientation, rising urbanization and profit orientation were acting as main driving forces for future changes in the farming sector of Haryana.